Evaluation of the toxicity of prorocentrum species by liquid chromatography mass-spectrometry and cell-based assay - Caillaud, A.; Canete, E.; Mallat, E.; Fernandez, M.; Mohammad Noor, Normawaty; Moestrup, Ojvind; Franco, J.M. (2006)
Dinoflagellates belonging to the genus Prorocentrum were studied for toxicological and toxin production properties by cell assays and liquid chromatographic methods, using fluorescence and mass-spectrometry detection (LC-FD, LC-MS). Cytotoxicity characterised by IC50 and morphological changes was examined. IC50 ranged from 2.103 cell equivalents mL-1 for P. cf faustiae to 133.103 for P. rhathymum. Morphological changes such as rounding and membrane blebbing were observed in fibroblasts exposed to Prorocentrum belizeanum and all Prorocentrum lima from Malaysia suggesting the presence of okadaic acid (OA). Analytical measurements confirmed the production of OA. However toxicity not correlated with the presence of OA suggests the production of derivates of OA or others toxin.